Telomerase/myocardin expressing mesenchymal cells induce survival and cardiovascular markers in cardiac stromal cells undergoing ischaemia/reperfusion. Issue 12 (5th May 2021) - Madonna, Rosalinda; Guarnieri, Simone; Kovácsházi, Csenger; Görbe, Aniko; Giricz, Zoltán; Geng, Yong‐Jian; Mariggiò, Maria Addolorata; Ferdinandy, Péter; De Caterina, Raffaele
Abstract: Cardiac stromal cells (CSCs) contain a pool of cells with supportive and paracrine functions. Various types of mesenchymal stromal cells (MSCs) can influence CSCs in the cardiac niche through their paracrine activity. Ischaemia/reperfusion (I/R) leads to cell death and reduction of the paracrine activity of CSCs. The forced co‐expression of telomerase reverse transcriptase (TERT) and myocardin (MYOCD), known to potentiate anti‐apoptotic, pro‐survival and pro‐angiogenic activities of MSCs isolated from the adipose tissue (AT‐MSCs), may increase CSC survival, favouring their paracrine activities. We aimed at investigating the hypothesis that CSCs feature improved resistance to simulated I/R (SI/R) and increased commitment towards the cardiovascular lineage when preconditioned with conditioned media (CM) or extracellular vesicles (EV) released from AT‐MSCs overexpressing TERT and MYOCD (T/M AT‐MSCs). Murine CSCs were isolated with the cardiosphere (CSps) isolation technique. T/M AT‐MSCs and their secretome improved spontaneous intracellular calcium changes and ryanodine receptor expression in aged CSps. The cytoprotective effect of AT‐MSCs was tested in CSCs subjected to SI/R. SI/R induced cell death as compared to normoxia (28 ± 4 vs 10 ± 3%, P = .02). Pre‐treatment with CM (15 ± 2, P = .02) or with the EV‐enriched fraction (10 ± 1%, P = .02) obtained from mock‐transduced AT‐MSCs in normoxia reduced cell death after SI/R. The effect was more pronounced with CM (7 ± 1%, P = .01) or the EV‐enriched fraction (2 ± 1%, P = .01) obtained from T/M AT‐MSCs subjected to SI/R. In parallel, we observed lower expression of the apoptosis marker cleaved caspase‐3 and higher expression of cardiac and vascular markers eNOS, sarcomeric α‐actinin and cardiac actin. The T/M AT‐MSCs secretome exerts a cytoprotective effect and promotes development of CSCs undergoing SI/R towards a cardiovascular phenotype.